Electroencephalographic analysis of the functional conectivity in habituation by graphics theory - Alducin Castillo, J.; Yanez Suárez, O.; Brust Carmona, H. (Revista Mexicana de Ingenieria Biomedica, 2016)
The hypothesis that the brain works using glial-neuronal networks that are responsible for sensory, motor and cognitive processes has been proposed in the neuroscience literature. Graph theory offers mathematical models to describe these complex networks from simple abstractions such as nodes and connecting edges. In this work, using signal processing techniques to the analysis of functional connectivity between neuronal ensembles derived from EEG measurements through theory graph. Procedures for the analysis of connectivity are described, from multichannel record processing and conditioning, computation of wideband power spectral density, determination of connectivity measures between electrodes, and parameter estimation of the resulting complex networks. EEG recordings from fifty subjects were analyzed in intervals before (pre) and during repeated photostimulation (Rph). Based on the statistical significance of the response during Rph, desynchronization/synchronization (D/S) in alfa band, and its wide distribution in cortical areas, the participants were divided into three groups: G1 , G2 and G3. The slope D/S in alfa band was significant in 16 of 16 regions (G1), 12 of 16 (G2) and 5 of 16 (G3). The functional connectivity depicted the same trend as these changes, whereas in the delta, theta and beta bands occurred no modifications. D is related to activation and S with inhibition, supporting the hypothesis of alfa-band’s participation in the cognitive process of habituation to photostimulation.